How Blockchain and Microservices are Being Used Together: a Systematic Mapping Study - Santos, Rayane; Soares, Pamella; Rodrigues, Evandro; Maia, Paulo Henrique M.; Silveira, Amanda (Proceedings of the 5th International Workshop on Emerging Trends in Software Engineering for Blockchain, 2022)
Microservices and blockchain are recent technologies that are at-tracting attention not only individually, but also when used together to achieve a certain goal. This study aims to map how both tech-nologies have been integrated with applications, presenting the state of the art in the subject. To do that we conducted a system-atic mapping study that searched five significant research bases and selected 40 papers to extract information. The results indicate that healthcare has been the most addressed domain using the combination of blockchain and microservices. On the other hand, the majority of studies have not been evaluated or presented only a proof of concept as an empirical validation, which shows that the proposals are not mature yet and there are still open research opportunities.